Critical thinking skills of prospective biology teacher on the chromosomal basic of inheritance learning through online discussion forums. Issue 2 (February 2019) - Maryuningsih, Y; Hidayat, T; Riandi, R; Rustaman, N Y
Abstract: Critical thinking skill (CTS) are 21st century skills, need to be trained on prospective teachers as stock of life in the future. With online forum discussion apps, prospective teachers apply multifunctional smartphones to help the learning process and practice their critical thinking skills. The role of online discussion forums is studied to investigate students' perceptions of the use of smartphones in supporting the learning process. Nevertheless it is rarely used to investigate the level of CTS of prospective teachers. A quasi experiment study to investigate the level of CTS of students through online discussion forum was conducted on prospective teachers who take Genetics course with 37 prospective teachers selected by purposive sampling a participants. This research focus is implementing online discussion forums through smartphone-assisted applications short message. Problem-based online discussion forums with three different cases are applied on Chromosomal Basic Inheritance Learning. Data acquisition of CTS of prospective teachers is obtained through the participants' responses in responding to problems in the online discussion forum and then analyzed to determine the level of CTS of prospective teachers according to the Facione CTS assessment tool. The prospective teacher's critical thinking skill level increases on the basic of chromosomal inheritance learning properties through online discussion forums.